A Critical Review of the Technical Characteristics of Recycled Brick Powder and Its Influence on Concrete Properties - Jinkang Hu; Wisal Ahmed; Dengwu Jiao (Buildings)
This paper presents a systematic overview of the applications of RBP as a substitute for cement. Initially, the fundamental properties of RBP, including physical properties, chemical compositions, and morphology, are discussed. Subsequently, the effects of RBP on various aspects of cement-based materials, such as fresh properties, shrinkage behavior, hydration, microstructure, strength development, and durability, are thoroughly reviewed. The findings of this study reveal that waste brick powder exhibits pozzolanic activity and can be used to partially replace cement in concrete formulations. However, its relatively high water absorption and irregular shape increase the water demand and, thus, reduce the rheological properties. The incorporation of RBP with 10–20% or finer particle sizes can refine the pore structure and promote the formation of hydration products. However, replacements of RBP greater than 25% can lead to adverse effects on the mechanical properties, frost resistance, and carbonation resistance of cementitious composites. Therefore, to enhance the effectiveness of RBP, measures such as improving fineness, incorporating mineral admixtures, adjusting curing conditions, and applying nano- or chemical modifications are necessary. This study provides valuable technical support for promoting the sustainable preparation of construction materials, which holds important environmental and economic implications.